Performance improvement of transcritical vapor generator by a novel double-heated annular configuration - Yue Pan; Yuling Zhai; Zhouhang Li; Nan Hu (Case Studies in Thermal Engineering)
A novel double-heated annular configuration is proposed for the vapor generator of transcritical CO2 power cycle. The idea originated from that an annulus is more resistant to the deterioration of supercritical heat transfer than a circular tube, and in this work attempts were made on adjusting the heating mode to potentially further improve the thermal efficiency. Numerical results from the present well-validated model show that in forced convection flow, the introduction of outside heating surprisingly increase the heat transfer coefficient at the inner side, with a maximum relative rise of 17 % to that with only inner heating. This enhancement owes to the more favorable radial profiles of fluid thermophysical properties, with specific heat and Prandtl number near the inner side being significantly increased by the outer heating. In mixed convection flow, the double-side heating improves the inside heat transfer when the outside heat flux is below 40 % of the critical heat flux in circular tubes, otherwise it may impair heat transfer, the extent of which depends on the specific operating conditions and geometric parameters. As the outside heat flux increases, wall temperatures at both annular sides gradually evolve into a similar profile to that of circular tubes. However, even when both sides are subjected to the critical heat flux, the peak wall temperatures are still 2–30 K lower than those of circular tubes. The heat transfer deterioration is not exacerbated even at the worst scenario, demonstrating the superior anti-deterioration performance of the double-heated annular configuration. Overall, the novel configuration can effectively improve supercritical heat transfer once designed as recommended, substantiating itself as a feasible option for transcritical heat exchangers.